Pemodelan Dan Perhitungan Volume Akuifer Dengan Menggunakan Metode Indicator Kriging Di Kec. Koto Tangah Dan Kec. Pauh Kota Padang - Hedsing Cressendo; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Groundwater is a very useful resource for all living things on earth. Living things, especially humans, do various ways to meet the needs of water. Based on its existence in this world, water is something that is needed by humans. The conditions of the place of residence vary, not all regions have sufficient water resources, so there are certain areas that experience difficulties with water resources. Population growth in the city of Padang has resulted in the expansion of housing development which has led to an increase in water demand, which can lead to a decrease in groundwater levels due to excessive withdrawal. This study aims to model and calculate the volume of the aquifer layer at several points in the study location. Based on data from the results of the drill log test at several points in the district Koto Tangah and Pauh distric area which will later be made in 3D modeling using SGeMS software and calculate the volume of the aquifer layer using the Krigging Indicator Method 3D modeling was obrained using the kriging indicator method in the Koto Tangah District area with the result of and aquifer volume of 2.531250m3 and 1.282.500m3 fo the Pauah District area.Keywords: Groundwater, aquifer layer, drill log, SGeMS, Indicator Kriging.